METTL3 Regulates Osteoblast Differentiation and Inflammatory Response via Smad Signaling and MAPK Signaling - Zhang, Yiwen; Gu, Xiaofei; Li, Di; Cai, Luhui; Xu, Qiong (International journal of molecular sciences, 2019)
Osteoblasts are crucial bone-building cells that maintain bone homeostasis, whereas inflammatory stimuli can inhibit osteogenesis and activate inflammatory response. N6-methyladenosine (m6A) is the most abundant mRNA modification in eukaryotes and plays important roles in multiple biological processes. However, whether m6A modification affects osteoblast differentiation and inflammatory response remains unknown. To address this issue, we investigated the expression of the N6-adenosine methyltransferase METTL3 and found that it was upregulated during osteoblast differentiation and downregulated after LPS stimulation. We then knocked down METTL3 and observed decreased levels of osteogenic markers, ALP activity, and mineralized nodules, as well as Smad1/5/9 phosphorylation, in LPS-induced inflammation. METTL3 knockdown promoted the mRNA expression and stability of negative regulators of Smad signaling, Smad7 and Smurf1, the same regulatory pattern identified when the m6A-binding protein YTHDF2 was silenced. Moreover, METTL3 depletion enhanced proinflammatory cytokine expression and increased the phosphorylation of ERK, p38, JNK, and p65 in MAPK and NF-κB signaling pathways. The increase in cytokine expression was inhibited after MAPK signaling inhibitor treatment. All data suggest that METTL3 knockdown inhibits osteoblast differentiation and Smad-dependent signaling by stabilizing Smad7 and Smurf1 mRNA transcripts via YTHDF2 involvement and activates the inflammatory response by regulating MAPK signaling in LPS-induced inflammation.